Morbidity and mortality in patients with acute pancreatitis. Cienfuegos, 2014-2015 - Daniel Felipe Marín Ríos; Orlando Manuel Águila Meleros; Lidia Torres Ajá; José Alberto Puerto Lorenzo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Acute pancreatitis is an inflammatory process that affects the pancreatic gland. It is associated with high rates of morbidity and mortality, despite the great advances in the management of critical patients in recent years. Objective: to characterize morbidity and mortality in patients diagnosed with acute pancreatitis. Methods: a descriptive, retrospective and correlational study of patients admitted with a diagnosis of acute pancreatitis in the 2014-2015 period in the General Surgery Department of the Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos. The variables analyzed were age, sex, skin color, clinical presentation, etiology, risk factors, complications, surgery requirement, time to admission to the intensive care unit, and discharge condition. Results: predominance of males (55.5%) and patients aged between 31-50 years (34.1%) was observed. The most frequent clinical presentation was mild (65.4%). The main etiology was vesicular lithiasis (40.7%). Among local complications, the acute necrotic collection was the most frequent, especially in severe cases (66.7%). Mortality was zero for mild and moderate cases, but increased to 63.3% in severe cases. Conclusion: the severity of acute pancreatitis is not related to its etiology; Local complications and mortality are greater in severe cases. Patients with mild acute pancreatitis usually have no relevant findings on computed tomography.